PRODUCTION OF POLYCLONAL ANTIBODY TO THE COAT PROTEIN OF CITRUS TRISTEZA VIRUS IN CHICKEN EGGS - Nurhadi Nurhadi; Kamaruzaman Sijam; Inon Sulaiman (Indonesian Journal of Agricultural Science, 2003)
Citrus tristeza virus (CTV) is one of the most destructive diseases in many citrus growing areas of Indonesia. Effective strategies for controlling CTV depend on diagnostic procedure namely enzyme-linked immunosorbent assay (ELISA). Study aimed to purify the CTV antigen and produced its polyclonal antibody. Virion of the severe CTV isolate designated UPM/ T-002 was concentrated by polyethylene glycol (PEG) precipitation combined with low speed centrifugation. Semipurified antigen was further purified by sodium dodecyl sulphatepolyacrylamide gel electrophoresis (SDS-PAGE). The specific coat protein (CP) band of CTV with molecular weight of 25 kD was excised and eluted using elution buffer containing 0.25 M Tris-HCl pH 6.8 + 0.1% SDS, then used as antigen for injection into 6-month-old female of White Leghorn chicken. Results, showed than the specific polyclonal antibody raised against the 25-kDa CP had a titer of approximately 104, gave low background reaction with healthy plant sap and reacted specifically with CTV isolates. The reaction was equally strong for a severe, a moderate, a mild, and a symptomless isolate, suggesting a broad reaction range of this antibody toward different CTV isolates. Optimal virus titer can be obtained since virus loss during purification could be minimized and the highly purified antigen as an immunogen could be obtained by cutting out the CP band from SDS-PAGE gels. Large amount of highly titer of CTV antibody can be produced in chicken egg. The simplicity of the procedure makes it economically acceptable and technically adoptable because the antibody can be produced in basic laboratory.